(untitled) (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: To determine the comparative energy value of discarded potato chips (DPC) used as a feed ingredient, the growth performance, carcass traits, and visceral mass were evaluated in 48 lambs. Materials and Methods: Lambs (29.89 ± 2.72 kg) were used in a randomized block design (8 replicates/treatment) in a 63-day feeding trial. DPC was composed mainly of malformed potato chips, which were removed before packaging. Its chemical composition was 96.92% dry matter, 7.11% CP, 39.65% ether extract, 2.84% neutral detergent fiber, and 46.03% starch. The DPC was included at 0%, 5%, and 10% in a total mixed ration (88:12 concentrate-to-forage ratio), replacing cracked corn grain. Results: Replacing corn with DPC did not affect dry matter intake (DMI), average daily gain, and gain-to-feed ratio. The observed dietary net energy (NE) was not modified by replacing corn with DPC and was close to (0.99) the NE expected according to the diet formulation. Using the replacement technique, the estimated NE for maintenance of DPC averaged 2.37 Mcal/kg. Kidney-pelvic-heart fat (KPH) and visceral fat were increased linearly (p = 0.04) as DPC increased in the diet, while the rest of the variables of carcass, shoulder tissue composition, and visceral mass were not affected. Conclusion: DPC included at up to a 10% level in the diet did not affect DMI, efficiency, and carcass traits but increased KPH and visceral fat. The average NE value of DPC is approximately 6.5% higher than that of cracked corn grain. However, due to its high fat content, careful consideration is necessary when formulating rations. J. Adv. Vet. Anim. Res., 12(4): 1405–1413, December 2025 http://doi.org/10.5455/javar.2025.l1000